Effects of acclimation and diapause on the cold tolerance of Trogoderma granarium. Issue 2 (15th January 2018) - Wilches, D.M.; Laird, R.A.; Floate, K.D.; Fields, P.G.
Abstract: Khapra beetle, Trogoderma granarium Everts (Coleoptera: Dermestidae), is a pest of stored grain in Africa, Asia, and Europe. It is a quarantine insect for much of the rest of the world. Control of T. granarium can be achieved with methyl bromide, but this fumigant is an ozone‐depleting substance and is being phased out worldwide. Thus, there is an urgent need to find new methods of control, including the use of low temperatures. Here, we assess the effects of diapause and cold acclimation on the cold tolerance of T. granarium . The percentage of larvae in diapause increased with larval density, reaching 57.3% when reared at a density of 73 larvae g −1 diet. The cold tolerance of T. granarium was assessed by the supercooling points (SCPs) of various life stages. The SCP of non‐acclimated insects ranged from −26.2 ± 0.2 °C (mean ± SEM) for eggs to −14.4 ± 0.4 °C for larvae. The lowest SCP for larvae, −24.3 ± 0.3 °C, was obtained for diapausing‐acclimated larvae. Based on mean LT50 values, the most cold‐tolerant stage at −10 °C was the diapausing‐acclimated larvae (87 days) followed by non‐diapausing‐acclimated larvae (51 days), diapausing non‐acclimated larvae (19 days), adults (4 days), non‐diapausing non‐acclimated larvae (2 days), pupae (0.4 days), and eggs (0.2 days). The estimated times to obtain 99.9968% mortality (Probit 9) for diapausing‐acclimated larvae are 999, 442, 347, 84, and 15 days at 0, −5, −10, −15, and −20 °C, respectively. Probit 9 is an estimated value used by quarantine experts to estimate conditions that are required to kill all insects. In light of the long exposure time needed to control T. granarium even at −20 °C, cooling to below −27 °C (i.e., below the SCP of eggs) will quickly kill all life stages and may be the best way to control this insect with low temperatures.